Intratumoral injection of holmium-166 microspheres as neoadjuvant therapy of soft tissue sarcomas in dogs - Morsink, Nino Chiron; Nijsen, Johannes Frank Wilhelmus; Grinwis, Guillaume Cornelis Maria; Hesselink, Jan Willem; Kirpensteijn, Jolle; van Nimwegen, Sebastiaan Alexander (Frontiers in Veterinary Science, 2022)
Introduction: Minimally invasive microbrachytherapy is in development to treat solid tumors by intratumoral injection of (radioactive) holmium-166 (166Ho) microspheres (MS). A high local dose can be administered with minimal damage to surrounding tissue because of the short soft tissue penetration depth of 166Ho beta radiation. We aimed to prospectively evaluate the safety and efficacy of 166Ho microbrachytherapy in client-owned canine patients with soft tissue sarcomas (STS). Methods: We included seven dogs with STS not suitable for local excision due to tumor size and/or location. 166HoMS were suspended in a carrier fluid and multiple needle-injections were performed in predetermined tumor segments to maximize tumor coverage. Tumor response was evaluated using 3D caliper and CT measurements. Follow-up further included monitoring for potential side-effects and registration of subsequent treatments and survival, until at least two years after treatment. Results: Delivered radioactive doses ranged from 70 to 969 Gy resulting in a mean tumor volume reduction of 49.0 ± 21.3% after 33 ± 25 days. Treatment-related side effects consisted of local necrosis (n=1) and ulceration of the skin covering the tumor (n=1), which resolved with basic wound care, and surgical excision of residual tumor, respectively. Residual tumor was surgically resected in six patients after 22 to 93 days. After a mean follow-up of 1005 days, four patients were alive, two patients were euthanized because of unrelated causes, and only one patient was euthanized because of disease progression after the owner(s) declined subsequent surgical treatment. Conclusion: 166Ho microbrachytherapy was a safe and effective neoadjuvant treatment option for canine patients with STS.